THE USE OF INQUIRY-BASED STUDENT WORKSHEET TO INSTILLS SCIENCE GENERIC SKILL OF THE STUDENTS - Khabibah, Nurul; jalmo, Tri; Suyatna, Agus; Suyatna, Agus (International Journal of Research -GRANTHAALAYAH, 2018)
This research aims to develop inquiry-based student worksheet and to describe its attractiveness, usefulness and effectiveness. The development design uses seven steps of Borg & Gall research including research and data collection, planning, product draft development, initial field testing, revision of the test results, field testing, and product improvement. Product validation includes material validation, design and content using questionnaires. The subjects of the testing are teachers and students of one of state senior high schools in East Lampung. The results of material validation, design and student worksheet’s content are included in high category, so that it can be stated that the student worksheet is worth to use. The results of field testing indicated that inquiry-based student worksheet can instill students’ science generic skills in static fluid subject. Teachers’ and students’ responses towards the development results were 78% which was categorized as very attractive and 78% as very useful. From the results of effectiveness test, it was known that post-test values was higher than the mean of pre-test value. Therefore, the product which has been developed in the form of inquiry-based student worksheet is effective to instill science generic skill of the students.